EFFECTIVE METHODS OF TEACHING FOREIGN LANGUAGES TO SLOW-LEARNING UZBEK-SPEAKING LEARNERS AND THE ROLE OF RELIGION, GENDER, AND CULTURE - Ra’no Urishevna Madzidova; Eldorbek Davlatjon’s son Khusanov (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. Are you, as a foreign language teacher, experiencing challenges in teaching foreign languages to school students? Does working with slow learners in your classroom particularly concern you? Do issues such as low learning achievement, lack of motivation, and the influence of cultural and social factors affect your teaching process? If these questions sound familiar, then this academic article is written especially for you. Building on these practical concerns, the present study examines effective methods of teaching foreign languages to low-achieving Turkic-speaking learners through an interdisciplinary framework combining philology and pedagogics. The article analyzes common linguistic difficulties faced by Turkic-speaking students, including phonological, lexical, and grammatical interference, which often impede successful foreign language acquisition, particularly among slow learners in school environments. From a pedagogical perspective, the study highlights the importance of differentiated instruction, scaffolded learning activities, and learner-centered approaches aimed at increasing motivation and academic engagement. Special attention is given to the role of religion, gender, and culture as key socio-cultural factors influencing learners’ attitudes toward foreign language education. Respect for religious values, the application of gender-sensitive teaching strategies, and the integration of culturally relevant materials are discussed as effective means of reducing affective barriers such as anxiety and low self-confidence.